Effects of biofertilizer and water-saving irrigation interactions on the leaf photosynthesis and plant growth of tomatoes - Chen, Danyan; Ai, Yuchun; Li, Peizhe; Dong, Yue; Li, Hailing; Wang, Changyi; Jiang, Xiaorui; Li, Shilong; Shen, Yan; Dai, Aijun; Feng, Yuanyuan (International Journal of Agricultural and Biological Engineering, 2024)
Irrigation and fertilizer interaction is an efficient cultivation management strategy for facility agriculture. However, the effects of irrigation and fertilizer management on tomato growth and its physiological factors remain unclarified. In this study, two irrigation patterns (W1, conventional irrigation; W2, water-saving irrigation) and four fertilizer application patterns (CF, chemical fertilizer; BOF, biological organic fertilizer; NPK, nutrient compound fertilizer; BOF+NPK) were selected to observe the effects of their interaction on cherry tomato plant growth, leaf photosynthesis and fruit quality through pot experiments. The results showed that W2 treatments promoted plant height growth compared to W1 under the same fertilizer addition. Moreover, irrigation and fertilizer management had significant effects on net photosynthetic rate, intercellular oxidation concentration, stomatal conductance and transpiration rate at the first sequence flowering and fruiting stages. The maximum tomato plant height (99.0 cm) was achieved under the irrigation and fertilizer pattern of BOF and W2, along with the highest fruit yield of 1.98 kg/plant, which was approximately 31.1% higher than the minimum yield under the combined CF and W2 treatment. Under W2 treatments, the application of either NPK or BOF increased the soluble sugar content of tomatoes. The structural equation models showed that the soil alkali hydrolyzed nitrogen could directly significantly affect the yield and soluble sugar. The findings suggest that optimization of irrigation-fertilizer interactions positively regulates tomato growth, providing an efficient model for tomato irrigation and fertilizer management and a reference for sustainable development of facility agriculture. Key words" irrigation-fertilization interaction; cherry tomato; plant height; leaf photosynthesis; fruit yield and qualityDOI: 10.25165/j.ijabe.20241702.7881Citation: Chen D Y, Ai Y C, Li P Z, Dong Y, Li H L, Wang C Y, et al. Effects of biofertilizer and water-saving irrigationinteractions on the leaf photosynthesis and plant growth of tomatoes. Int J Agric & Biol Eng, 2024; 17(2): 177–185.